1993
DOI: 10.1128/jb.175.5.1293-1302.1993
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and DNA sequence of the gene coding for Clostridium thermocellum cellulase Ss (CelS), a major cellulosome component

Abstract: Clostridium thermocellum ATCC 27405 produces an extracellular cellulase system capable of hydrolyzing crystalline cellulose. The enzyme system involves a multicomponent protein aggregate (the cellulosome) with a total molecular weight in the millions, impeding mechanistic studies. However, two major components of the aggregate, SS (M(r) = 82,000) and SL (M(r) = 250,000), which act synergistically to hydrolyze crystalline cellulose, have been identified (J. H. D. Wu, W. H. Orme-Johnson, and A. L. Demain, Bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 55 publications
3
53
0
Order By: Relevance
“…It is an exoglucanase (168-170, 231, 234). Sequencing of celS revealed an open reading frame of 2,241 bp encoding 741 amino acid residues with a predicted molecular weight of 80,670 (341,343). The sequence revealed that CelS belonged to a new cellulase family (341).…”
Section: Components S L and S Smentioning
confidence: 99%
See 1 more Smart Citation
“…It is an exoglucanase (168-170, 231, 234). Sequencing of celS revealed an open reading frame of 2,241 bp encoding 741 amino acid residues with a predicted molecular weight of 80,670 (341,343). The sequence revealed that CelS belonged to a new cellulase family (341).…”
Section: Components S L and S Smentioning
confidence: 99%
“…Of particular interest was our gene sequencing of S L (96,277) and the gene sequencing of S S (341).…”
Section: Components S L and S Smentioning
confidence: 99%
“…Three extensively characterized Cel48 cellulases were chosen as parents for construction of the SCHEMA recombination library: CelF [10] from the mesophile Clostridium cellulolyticum ATCC 35319, CelY [18] from the thermophile Clostridium stercorarium, and CelS (also known as CelA) [19] from the thermophile Clostridium thermocellum ATCC 27405.…”
Section: Cel48 Parental Enzymesmentioning
confidence: 99%
“…Recently, CelS, the most abundant catalytic subunit in cellulosomes of the cellulolytic thermophile Clostridiurn thermocellurn, was characterized as an exo-1,4-P-glucanase (Morag et al, 1991;Wang et al, 1993;Kruus et a/., 1995). Furthermore, CbhA and CbhB of Cellulomonas fimi Shen et al, 1995) and presumably CelF of Clostridium cellulolyticum were shown to represent this type of cellulolytic enzyme in mesophilic bacteria.…”
Section: Introductionmentioning
confidence: 99%